A new species of Apisa Walker, 1855 (Lepidoptera: Erebidae: Arctiinae) from Uganda with remarks on the apomorphies of the genus - Przystałkowska, Anna (Zootaxa, 2022)
A new species of Apisa Walker, 1855 from Uganda (East Africa) and Gabon (Central Africa) is described according to morphological characters and DNA barcode information. A diagnosis, detailed description, distribution, and illustrations of specimens and the male genitalia are provided. Diagnostic characters are found in wing shape, strongly marked wing venation and details of the male genital apparatus.                The DNA barcode sequences of twelve specimens of A. atrovenosa sp. n. are compared with other members of Apisa. Diagnostic characters of the genus are summarised and discussed for the first time with an emphasis on the lack of arolium as the obvious autapomorphy. This character is shown by SEM photographs.